Legal Effects of Default on Land and Building Sale and Purchase Agreement in PPJB - Pangestu, Mohammad Bagas Agy; Hertanto, Ari Wahyudi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Along with the increase in property prices in Indonesia every year, many people choose to buy houses with installment payments. Therefore, the sale and purchase process is carried out by making an agreement, namely the Sale and Purchase Binding Agreement (PPJB) before the signing of the Sale and Purchase Deed (AJB). However, over time there is a problem where one party does not implement the contents of the agreement or is called default. This research was conducted with the aim of knowing how the legal consequences caused by defaults in land and building sale and purchase agreements and how to resolve disputes due to defaults in land sale and purchase agreements. Using normative juridical research methods, it can be concluded: 1. Legal consequences arising from default in a sale and purchase agreement, especially if one party does not implement the contents of the mutually agreed sale and purchase agreement, then the party has violated the agreement so that it is called committing a default act. 2. Settlement of disputes due to default in the sale and purchase agreement, can be done through deliberation from the parties for the settlement of the obligations of the parties in dispute to then be fulfilled / realized / paid by the parties who are considered in default. In addition, a party who feels aggrieved by the other party in the sale and purchase agreement, has the right to sue the other party who does not carry out the contents of the agreement through the intercession of a court judge or through existing legal channels.